Proposal for an effective bus stop design at Hentian Bandar of Rapid Kuantan - Hemaambiegey, Gunasekgerin (2014)
A bus stop serves as an interchange area where a bus picks passengers who wait to go places from different places. At Hentian Bandar Rapid Kuantan, the bus stop has been a facility; where at present 44 busses are plying 13 routes daily back and forth to the bus stop. However, this bus stop was not sufficient to support the increased number of users as compared to the times before Rapid Kuantan buses were introduced. Through observation, the existing condition of the bus stop was investigated. Readings on manuals and checking on documents were done. This was to rationale in revising the bus stop design. Bus stop designs are elaborated in terms of the walkway width, capacity and the facilities. The walkway width was measured and the effective width of the walkway was calculated. Using the traffic counting method, the pedestrian volume was tabulated. The Level of Service of the walkway was identified to be at a very poor level. The same method was also done to the waiting area. Besides that, the facilities were improper to serve the public and the operation officer. A better design was proposed to improve the bus stop with an adequate width of walkway and better serving facilities.